Bringing managers closer to papers: Measuring the relevance of business and management research - Vílchez-Román, Carlos (2023)
This study aims to validate a data collection tool’s psychometric properties to explore whether business management research’s relevance is a high-order construct made up of its perceived interest and perceived relevance. The authors conducted a confirmatory factor analysis to validate a two-factor scale. The sample was composed of 148 MBA students from a Peruvian business school. Results showed the appropriate levels of validity and reliability and confirmed the usefulness of this data set for exploring the relationship between perceived interest and relevance. Businesses and schools can replicate the validated tool for reviewing their curricula and teaching practices, exploring the gap between business and management research results and advancing managers’ research literacy and evidence-based practice in business education and training.